The Oxford handbook of human capital - Burton-Jones, Alan.; Spender, J.-C. (Oxford : Oxford University Press, 2011)
This handbook provides a much needed, authoritative and inter-disciplinary survey of concepts, applications and research on human capital, the stock of human capabilities and knowledge found in organisations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human capital